2021
DOI: 10.1039/d0ce01632b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic degradation of methyl violet using two new 3D MOFs directed by different carboxylate spacers

Abstract: Two highly stable metal-organic frameworks (MOFs) assembled by a flexible 1,4-bis(2-methylimidazol-1-yl)butane (bib), and two different aromatic carboxylate coligands, namely [Zn(BDC-OH2)(bib)] (1) and [Cd3(BTC)2(bib)(DMF)3] (2) (H2BDC-OH2= 2,5-dihydroxyterephthalic acid, H3BTC = 1,3,5-benzenetribenzoic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…− ), which can degrade the MV into small molecules. 32,33 Table S1 † presents the predicted band positions of the AgGaIJS 1−x Se x ) 2 NCs based on the empirical formulas. 21,34 It can be found that their CB potential is more negative than the standard redox potential of O 2 /˙O 2 − (−0.33 eV), while VB potential is less positive than that of ˙OH/OH − (2.38 eV).…”
Section: Resultsmentioning
confidence: 99%
“…− ), which can degrade the MV into small molecules. 32,33 Table S1 † presents the predicted band positions of the AgGaIJS 1−x Se x ) 2 NCs based on the empirical formulas. 21,34 It can be found that their CB potential is more negative than the standard redox potential of O 2 /˙O 2 − (−0.33 eV), while VB potential is less positive than that of ˙OH/OH − (2.38 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the DE value, the MV removals obtained in this work were not as high as the use of other photocatalysts such as ZnO, PbTiO 3 , TiSiW 12 O 40 /TiO 2 , or 3D MOF [ 34 , 35 , 36 , 37 ]. The DE values by these photocatalysts were around 80–99%; in particular, the values obtained by ZnO and TiO 2 were 90% and 94% for 90 min of treatment [ 34 , 36 ].…”
Section: Resultsmentioning
confidence: 75%
“…As an example, the initial MV utilized in the use of PbTiO 3 was 5 ppm with the photocatalyst dose of 3 g/30 mL and the dosage of 0.3 g/L for 10 ppm of MV by ZnO [ 34 , 36 ]. In the other MV photodegradation experiment, the DE of 85% by 3D MOF at the dosage was 8 g/L for 5 ppm of MV [ 37 ]. As the photocatalyst dose utilized in this work was 1 g/L and the initial concentration of MV was 10 ppm, the DE in this work was in acceptable values (95.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Concludingly, the skeletal structure, charge, bulkiness, etc., of the ligand can give rise to various metal complex structures. The knowledge of creating various controlled structures will also enable the development of metal-organic frameworks (MOFs) and is expected to be useful in various applications [22][23][24][25][26][27][28][29], beyond the use of molecular complexes as homogeneous catalysts.…”
Section: Structures Of Metal Complexes and Ligand Designmentioning
confidence: 99%